2016
DOI: 10.1098/rspb.2015.2926
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic coevolution between quantitative and Mendelian traits

Abstract: Coevolution is relentlessly creating and maintaining biodiversity and therefore has been a central topic in evolutionary biology. Previous theoretical studies have mostly considered coevolution between genetically symmetric traits (i.e. coevolution between two continuous quantitative traits or two discrete Mendelian traits). However, recent empirical evidence indicates that coevolution can occur between genetically asymmetric traits (e.g. between quantitative and Mendelian traits). We examine consequences of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…This study also showed that small population sizes resulted in lower standing genetic variation, due to inbreeding and/or genetic drift. Similar effects of population size have been shown in mathematical models (Gomulkiewicz & Houle, ; Uecker & Hermisson, ; Yamamichi & Ellner, ) and experiments (Bell & Gonzalez, ; Cameron, Plaistow, Mugabo, Piertney, & Benton, ; Gonzalez & Bell, ; Low‐Décarie et al, ).…”
Section: Introductionsupporting
confidence: 69%
“…This study also showed that small population sizes resulted in lower standing genetic variation, due to inbreeding and/or genetic drift. Similar effects of population size have been shown in mathematical models (Gomulkiewicz & Houle, ; Uecker & Hermisson, ; Yamamichi & Ellner, ) and experiments (Bell & Gonzalez, ; Cameron, Plaistow, Mugabo, Piertney, & Benton, ; Gonzalez & Bell, ; Low‐Décarie et al, ).…”
Section: Introductionsupporting
confidence: 69%
“…This makes gradient dynamic models a good starting point for studying eco-evolutionary dynamics. But, because they do not specify gene-level processes, they may not capture all possible dynamics (e.g., see Levin and Udovic 1977, Doebeli 1997, Yamamichi and Ellner 2016.…”
Section: Assumptions and Generality Of Model And Resultsmentioning
confidence: 99%
“…This stabilizes allele fluctuations and enhances allele persistence under fluctuating selection (Figs. 1 and 2; see also Yamamichi and Ellner 2016 for antagonistic coevolution).…”
Section: Discussionmentioning
confidence: 99%
“…Time‐lagged NFDS is especially common in antagonistic coevolution in host–parasite or prey–predator interactions and is considered to be influential for balancing selection (Tellier and Brown ; Leffler et al. ; Yamamichi and Ellner ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation